Naturalne planowanie rodziny wewnętrznym aspektem odpowiedzialnego rodzicielstwa - Pryba, Andrzej (Verbum Vitae, 2022)
The article deals with a principled aspect of responsible parenthood, the decision to choose natural family planning as a method of birth control within the marital dialogue, and its consistent implementation through parental attitudes. The analysis of the research problem proceeds via four stages. First, the foreground lays out the solid theological, biblical and anthropological foundations of responsible parenthood. The second stage explores the multiple contexts of parental decisions, from the perspective of the determinants of marital dialogue. Next follows a presentation of the theological, ethical and psychological values of the natural family planning methods. Finally, an attempt is made to specify the essence of the parental decision, which implies the use of natural methods of birth control by the spouses. The hermeneutic key linking all the theological analysis of the article has been the concept of a personal gift on the part of the spouses. The conclusions we have formulated encompass the many dimensions – ethical, anthropological, theological, charismatic, and cultic-liturgical – of a married couple’s decision regarding a family planning strategy.